2008
DOI: 10.1253/circj.72.458
|View full text |Cite
|
Sign up to set email alerts
|

Altered Interaction Between Plasminogen Activator Inhibitor Type 1 Activity and Sympathetic Nerve Activity With Aging

Abstract: The study population comprised 16 young healthy subjects (all men: aged between 21 and 37 years, mean age 26.1 years) and 10 aged subjects (9 men, 1 woman; aged between 46 and 71 years, mean age 56.9 years). All aged subjects Circ J 2008; 72: 458 -462 (Received July 11, 2007; revised manuscript received October 16, 2007; accepted November 1, 2007 Background It has been reported that sympathetic nerve activity (SNA) is associated with fibrinolysis, but the interaction between SNA and the fibrinolytic system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…[28][29][30][31] Here we showed that aging is associated with the reduction of activity of only one of the various antioxidant enzymes. In addition, we investigated the association of aging with the tolerance of macrophages against oxLDL.…”
Section: Mnsod Activity and Macrophage Apoptosismentioning
confidence: 91%
“…[28][29][30][31] Here we showed that aging is associated with the reduction of activity of only one of the various antioxidant enzymes. In addition, we investigated the association of aging with the tolerance of macrophages against oxLDL.…”
Section: Mnsod Activity and Macrophage Apoptosismentioning
confidence: 91%
“…32 Sympathetic activity may promote coagulation (via downregulation of the fibrinolytic system). 33 Schwartz et al demonstrated that autonomic stress could trigger lethal ventricular arrhythmias in dogs with myocardial infarction. 6 These findings indicate that the activation of the sympathetic nervous system may be one of the promoters of those acute events, although not a main cause.…”
Section: Main Results and Comparison With Previous Studiesmentioning
confidence: 99%
“…5) Otowa et al demonstrated that hyperactivity of sympathetic nerve system increased PAI-1 activity under hypovolemic state. 6) Considering that PAI-1 is negative regulator for thrombolysis, shutdown of sympathetic activity influences the thrombosis-thrombolysis balance and may shift to thrombolytic state in the occluded artery. Moreover, recent study demonstrated that sympathetic vasoconstriction persisted and restrained muscle blood flow under hypoxia .7) Therefore, immediate ablation of the thoracic sympathetic ganglia may be effective for patients with acute digital arterial occlusion.…”
Section: Discussionmentioning
confidence: 99%